The Need For Formation of Knowledge on The Effective Use Of Water Resources in Young People in The Process of Globalization. (In The Example Of The Aral Sea) - Sharofiddin Shukurjon Ogli Shomurotov (Research Parks Publishers, 2021)
The article deals with the issues of intensive development of irrigation systems, effective management of water resources and improvement of irrigation infrastructure, application of agro-technical measures in agriculture, implementation of innovations to improve the reclamation of irrigated lands, efficient and rational use of water resources illuminated